2014
DOI: 10.1111/dom.12344
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin signalling in β‐cells regulates insulin secretion and blood glucose

Abstract: Insulin secretion from pancreatic islet β-cells is stimulated by glucose. Glucose-induced insulin release is potentiated or suppressed by hormones and neural substances. Ghrelin, an acylated 28-amino acid peptide, was isolated from the stomach in 1999 as the endogenous ligand for the growth hormone (GH) secretagogue-receptor (GHS-R). Circulating ghrelin is produced predominantly in the stomach and to a lesser extent in the intestine, pancreas and brain. Ghrelin, initially identified as a potent stimulator of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 45 publications
2
49
0
1
Order By: Relevance
“…Several studies have reported that H. pylori seropositivity was associated with different hormones [2,[8][9][10], most of which were involved in glucose metabolism directly or indirectly [11][12][13][14][15][16][17]. To our knowledge, at least three hormones supported our results, including gastrin, leptin and ghrelin.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Several studies have reported that H. pylori seropositivity was associated with different hormones [2,[8][9][10], most of which were involved in glucose metabolism directly or indirectly [11][12][13][14][15][16][17]. To our knowledge, at least three hormones supported our results, including gastrin, leptin and ghrelin.…”
Section: Discussionsupporting
confidence: 85%
“…Leptin has been reported to reduce hyperglycaemia in rodent models of type 1 diabetes and has recently been shown to normalise fasting plasma glucose concentrations in a rodent model of polygenic obesity and type 2 diabetes [14]. In contrast, ghrelin has been shown to upregulate systemic glucose levels in both humans and rodents [16]. Thus, studies reporting elevated gastrin and leptin and decreased ghrelin levels in individuals infected with H. pylori support our findings.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the chronic hypothyroid mice in our study did not produce elevated circulating ghrelin levels, there was clearly an effect of thyroid hormone deficiency to induce ghrelin locally within hESC-derived grafts. Pancreatic ghrelin serves as a local regulator of insulin release even though it may not contribute to the circulating ghrelin levels (20). Therefore, ghrelin may be acting in a paracrine manner to impair insulin secretion in the hESCderived grafts from chronic hypothyroid mice.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide is comprised of 28 amino acids with the unique feature of an n-octanoylated residue (serine-3) (Kojima et al, 1999). The numerous and diverse physiological roles of ghrelin consist of the stimulated pituitary release of growth hormone, increased food intake, mediation of energy homeostasis, enhanced gastrointestinal motility, and the regulation of systemic insulin levels and glycaemia (Kojima et al, 1999;Kirchner et al, 2012;Yada et al, 2014;Perello & Dickson, 2015;Alamri et al, 2016). To date, molecular biological studies have revealed that ghrelin is widely conserved in both mammals and nonmammals (Kojima et al, 2008).…”
Section: Introductionmentioning
confidence: 99%